Gyarmathy, Z., & Altshuler, D. (2020). (Non) culmination by abduction. Linguistics, 58(5), 1373-1411 - Zhang, Zichen (elingUP: Revista Eletrónica de Linguística dos Estudantes da Universidade do Porto, 2024)
.